(untitled) (ESMAT Magazine, 2025)
This article presents a critical analysis of Bill No. 2,159/2021, which proposes significant changes to the environmental licensing process in Brazil. Based on the discussion of the bill's key provisions, it becomes evident that, although there are specific advances aimed at modernization and transparency—such as the reactivation of SINIMA and the requirement for institutional reports—the project tends to weaken essential environmental control and oversight mechanisms. The expansion of scenarios exempt from licensing, the absence of a minimum list of activities subject to the process, and the delegation of responsibilities to developers illustrate a normative setback. It is concluded that, by prioritizing deregulation over environmental protection, the bill threatens the constitutional right to an ecologically balanced environment, posing risks to sustainability and the effectiveness of environmental policies in the country.